KOLABORASI UGM, UNIVERSITAS PETRA SURABAYA, UNCEN DAN UOGP SERTA PARTISIPASI MAHASISWA KKN DALAM PEMBUATAN MCK RAMAH LINGKUNGAN AKIBAT BENCANA ALAM KABUPATEN JAYAPURA - Agustinus Agustinus; Elisabeth Wambrauw; Elisabeth Payung Allo (JURNAL PENGABDIAN PAPUA, 2022)
The occurrence of flash floods in Sentani claimed many victims, some suffered minor and serious injuries that could not be counted, as well as many people's houses that were washed away and damaged so that the community was placed in refugee camps prepared by the government. To deal with the people affected by the flash floods that occurred in Sentani, the government could not reach out to the entirety to evacuate the evacuation sites that had been prepared. Some of the refugee campsprepared by the government do not have facilities for the community's necessities of life, namely MCK. Through this service, we are moving to conduct a field survey to see which locations can be helped to cope with life in refugee camps. The purpose of this service is to help small asey communities living in refugee camps who do not have MCK, so we encourage final semester Planology students to do KKN in that place to build environmentally friendly MCK. The materials used to build MCK houses are light steel, the process is easy to do. simple and practical. In this service, we provide training to students and the community how to cut canal C or mild steel using a hand grinder. Likewise in the assembly of bolts to the frame using a hand drill for both installation and removal if there is an error. This training is easily accepted and carried out by KKN students and the community, so that the making of MCK can be completed properly and used by the community of Kampung Asei Kecil Telaga Maya. In this service, together with KKN students, it really helps the government to overcome the lives of the people in refugee campus. Keywords: Mild steel; environmentally friendly MCK; Sentani